Risk and Risk Periods for Stroke and Acute Myocardial Infarction in Patients with Central Retinal Artery Occlusion - Park, Sang Jun; Choi, Nam-Kyong; Yang, Bo Ram; Park, Kyu Hyung; Lee, Joongyub; Jung, Sun-Young; Woo, Se Joon (Ophthalmology (Rochester, Minn.), 2015)
To investigate the risk of stroke and acute myocardial infarction (AMI) in patients with incident central retinal artery occlusion (CRAO). A self-controlled case series (SCCS) study. Patients with incident CRAO from the entire Korean population of 48 million individuals. We used the Korean national claim database (2007-2011) for analyses. After identifying patients with incident CRAO, the relative incidence rate ratios (IRRs) for stroke and AMI in risk periods were measured in these patients using a SCCS method. The IRRs of stroke and AMI by risk periods. Of 1655 patients with incident CRAO in 2009-2010, 165 had stroke/AMI (ischemic stroke in 139, hemorrhagic stroke in 13, and AMI in 15) in the observation period spanning 365 days before and after the occurrence of CRAO. The IRR of stroke/AMI 1 to 30 days after CRAO occurrence significantly increased (14.0; 95% confidence interval [CI], 8.90-22.00); the IRR peaked during the 1 to 7 days after CRAO occurrence (44.51; 95% CI, 27.07-73.20), and the increased risk was present for the first 30 days. The IRR of stroke/AMI also significantly increased 1 to 30 days (6.82; 95% CI, 4.01-11.60) and 31 to 90 days (2.86; 95% CI, 1.66-4.93) before CRAO occurrence. Subanalysis for only ischemic stroke showed similar, magnified IRRs in the risk periods compared with all events. The IRRs were not significantly different between sexes or age groups (<65 vs. ≥65 years). Patients with incident CRAO are at increased risk of ischemic stroke just after CRAO occurrence, and the risk is particularly increased during the first week immediately after the CRAO occurrence. The results suggest that patients with incident CRAO require immediate neurologic evaluation and preventive treatment to reduce mortality and morbidity.